Aplikasi Pendataan Pengunjung Perpustakaan Universitas Sam Ratulangi Manado Menggunakan Pemindai QR Code: Sam Ratulangi University Manado Library Visitor Data Collection Application Using a QR Code Scanner - Yeremia Senduk; Sherwin R. U. A. Sompie; Agustinus Jacobus (Universitas Sam Ratulangi, 2024)
The rapid development of Information Technology (IT) has an impact on almost all aspects of life. With the existence of information technology, in this case the internet, all information in the form of text, images, sound or video can be accessed or sent quickly. The Sam Ratulangi University Library (UNSRAT) is one of the places to support the lecture and research activities of students and lecturers managed by the university. Currently the Unsrat library uses attendance books for members registered at the library. The process of collecting data on visitors to the Unsrat Library still uses traditional data collection, namely writing visitor data in books by the library admin. This process has shortcomings that the author found, such as the attendance book being lost and the data not being backed up elsewhere, recapping visitor reports having to be done manually and taking a long time and there being no report on how long visitors spend in the library. QR Code is a matrix code that can store up to thousands of alphanumeric information. So, by just using one code we can store and get the information we need. Based on the problems previously presented, using QR Codes can be a solution to facilitate the visitor data collection process. Visitors' personal data can be stored on the internet and the process of collecting data on visit times can be done easily and quickly by using a QR Code. Here the author recommends that there is a need for an application for data collection on Unsrat library visitors using a QR Code scanner. Key words — Library; Data Collection; QR Code.